2018
DOI: 10.1080/15476286.2018.1536590
|View full text |Cite
|
Sign up to set email alerts
|

Dual DNA rulers reveal an ‘mRNA looping’ intermediate state during ribosome translocation

Abstract: The precise 3-nucleotide movement of mRNA is critical for translation fidelity. One mRNA translocation error propagates to all of the following codons, which is detrimental to the cell. However, none of the current methods can reveal the mRNA dynamics near the ribosome entry site, which limits the understanding of this important issue. We have developed an assay of dual DNA rulers that provides such capability. By uniquely probing both the 3ʹ- and 5ʹ-ends of mRNA, we observed an antibiotic-trapped intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The 3 bp difference was caused by the normal translocation step in which three more nucleotides on the mRNA would be covered by the ribosome in the Post and could no longer hybridize with the probing DNA (Figure A, bottom). If frameshifting occurred, we would observe a 13 bp duplex for −1 frameshifting, or a 14 bp duplex for −2 frameshifting, as we have demonstrated in previous publications . The results of the ribosome positions and their corresponding percentages are shown in Figure B.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The 3 bp difference was caused by the normal translocation step in which three more nucleotides on the mRNA would be covered by the ribosome in the Post and could no longer hybridize with the probing DNA (Figure A, bottom). If frameshifting occurred, we would observe a 13 bp duplex for −1 frameshifting, or a 14 bp duplex for −2 frameshifting, as we have demonstrated in previous publications . The results of the ribosome positions and their corresponding percentages are shown in Figure B.…”
Section: Resultssupporting
confidence: 69%
“…We investigated the effect of reduced power strokes on translocation by identifying the exact ribosome movement on the mRNA. The probing scheme is shown in Figure A, which has been used in our previous publications . Briefly, the ribosome position was revealed by the number of bp between the exposed mRNA and the probing DNA; the number of bp was deduced from the critical force of the duplexes obtained by FIRMS.…”
Section: Resultsmentioning
confidence: 99%
“…The 5'-end DNA rulers contained a 50-nt linker to overcome the steric hindrance between the surface and the ribosome. [13] The precise lengths of the mRNA uncovered by the ribosome were determined by the dissociation forces of the DNA-mRNA duplexes. Therefore, the ribosome footprints will be deduced.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation of the duplex dissociation force and the ribosome's coverage on the mRNA has been demonstrated earlier, in which we found that the ribosome covers 27 nt in the pre-and post-states, while the first mRNA nt out of the leading edge (3'-end) is + 12 from the first nucleotide in the P-site. [13,18] Force spectra of the duplexes were obtained by measuring the magnetic signal of the sample as a function of acoustic radiation force exerted on the duplexes via the magnetic bead, in which the dissociation force was indicated by a decrease of the magnetic signal. Figure 1b shows the force spectra of DNA rulers that formed 12-bp duplex with the 5'-end mRNA, in the presence and absence of the ribosome in the pre-translocation state (Pre).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation